The diet and landclass affinities of the Irish hare Lepus timidus hibernicus - Dingerkus, S. K.; Montgomery, W. I. (Journal of Zoology, 2001)
Abstract The diet of the Irish hare Lepus timidus hibernicus was investigated in Northern Ireland. Faecal pellets were collected at regular intervals from three contrasting study sites and from a number of randomly selected sites from known land classes. Microhistological techniques were employed to analyse the pellets. Grass species occurred in high percentage frequencies in all samples of faecal pellets and a wide variety of plant species were represented (up to 26 species in one study site). In a stratified, random survey of the presence of hares, areas of lowland intensive agriculture had fewer positive records than expected. It is contended that L. t. hibernicus may not be able to sustain viable populations in areas of intensive agriculture, which are almost exclusively composed of ryegrass Lolium spp.